A computer‐based model to assess costs associated with the use of factor VIII and factor IX one‐stage and chromogenic activity assays. (18th February 2016) - Kitchen, S.; Blakemore, J.; Friedman, K. D.; Hart, D. P.; Ko, R. H.; Perry, D.; Platton, S.; Tan‐Castillo, D.; Young, G.; Luddington, R. J.
Abstract : Essentials Chromogenic factor VIII and factor IX assays have not been widely adopted partly due to perceived cost. Chromogenic assays may be needed for monitoring therapy with some extended half‐life concentrates. Efficient use of reagents makes the costs of chromogenic and one‐stage factor IX assays similar. A similar approach for factor VIII delivers lower costs for chromogenic compared with one‐stage assays. Summary: Background: Measurement of coagulation factor factor VIII (FVIII) and factor IX (FIX) activity can be associated with a high level of variability using one‐stage assays based on activated partial thromboplastin time (APTT). Chromogenic assays show less variability, but are less commonly used in clinical laboratories. In addition, one‐stage assay accuracy using certain reagent and instrument combinations is compromised by some modified recombinant factor concentrates. Reluctance among some in the hematology laboratory community to adopt the use of chromogenic assays may be partly attributable to lack of familiarity and perceived higher associated costs. Objectives: To identify and characterize key cost parameters associated with one‐stage APTT and chromogenic assays for FVIII and FIX activity using a computer‐based cost analysis model. Methods: A cost model for FVIII and FIX chromogenic assays relative to APTT assays was generated using assumptions derived from interviews with hematologists and laboratory scientists, common clinical laboratory practise, manufacturer list prices and assay kit configurations. Results: Key factors that contribute to costs are factor‐deficient plasma and kit reagents for one‐stage and chromogenic assays, respectively. The stability of chromogenic assay kit reagents also limits the cost efficiency compared with APTT testing. Costs for chromogenic assays might be reduced by 50–75% using batch testing, aliquoting and freezing of kit reagents. Conclusions: Both batch testing and aliquoting of chromogenic kit reagents might improve cost efficiency for FVIII and FIX chromogenic assays, but would require validation. Laboratory validation and regulatory approval as well as education and training in the use of chromogenic assays might facilitate wider adoption by clinical laboratories.